(untitled) (American Journal of Islam and Society, 2003)
The 36th annual meeting of the Middle East Studies Association of North America (MESA), was held at the Wardman Park Hotel, Washington, DC, November 23-26, 2002. This conference, possibly the largest gathering of scholars and students of the Middle East, took place in an atmosphere saturated by 9/11 and Washington’s plans for an all-out war against Iraq, as well as considerable right-wing and pro-Zionist pressure applied by such members of the epistemic community of scholars, journalists, and policy analysts as Daniel Pipes (the Middle East Forum) and Martin Kramer, a one-time director and currently a senior research fellow at Tel Aviv University’s Moshe Dayan Center for Middle Eastern and African Studies. Both are behind Campus Watch (http://www.campus-watch.org), which monitors academic discourse that opposes American foreign policy toward the Muslim world and its one-sided support for Israel, and which maintains on its website a list of “un-American” academicians and apologists for “militant Islam” and rogue regimes. November 23, the first day, was reserved for the business meetings of all groups having an institutional affiliation with MESA. The panels, presented as parallel sessions, began on Sunday at 8:30 a.m. Also featured was a presidential address by the outgoing president, a plenary session, a book exhibition, an art gallery, and a film fest. MESA organizers reported that 1,900 people attended the 156-panel event, along with 80 exhibitions. The first session featured panels on popular culture and identity in the Maghreb, women and development, issues in contemporary Iran, intellectuals and ideas in the making of the Turkish Republic, history of the Ottoman borderlands, legitimation of authority in early period of Islam, comparative perceptions of the “other” in Israeli and Palestinian textbooks, comparative analysis of political Islam, religious conversion and identity, and the Arabic qasidah. There was also a roundtable discussion on water issues and a thematic conversation on 9/11 and the Muslim public sphere. In the following ...